All‐Solid‐State Batteries: Low Resistance–Integrated All‐Solid‐State Battery Achieved by Li7La3Zr2O12 Nanowire Upgrading Polyethylene Oxide (PEO) Composite Electrolyte and PEO Cathode Binder (Adv. Funct. Mater. 1/2019). (2nd January 2019) - Wan, Zipei; Lei, Danni; Yang, Wei; Liu, Cheng; Shi, Kai; Hao, Xiaoge; Shen, Lu; Lv, Wei; Li, Baohua; Yang, Quan‐Hong; Kang, Feiyu; He, Yan‐Bing
Abstract : In article number1805301, Yan‐Bing He and co‐workers report a low resistance integrated all‐solid‐state Li metal battery with excellent electrochemical performance. The battery structure applies polyethylene oxide with lithium bis(trifluoromethylsulphonyl)imide as both the binder of the cathode and matrix of the composite electrolyte embedded with Li7 La3 Zr2 O12 nanowires.